Sensory Quality Test of Liquid Eggs Preservation by Adding Forest Bee Honey and Cold Storage - Saputri, Kade Wahyu; Nur’aini, Nur’aini (Universitas Bengkulu, 2025)
To extend their shelf life beyond the approximate 14 days they last at room temperature, fresh eggs are often processed into liquid eggs. Storage at 4°C with the addition of forest honey (Apis dorsata), which is rich in antibacterials, antioxidants, and sugars, has the potential to maintain quality and serve as a sugar substitute in food products. This study evaluated the sensory quality of liquid eggs with forest honey after cold storage. A total of 60 chicken eggs were stored at 4°C for 21 days. Sensory testing was conducted on 21-day-old liquid eggs that had been steamed for 30 minutes. Panelists assessed color, aroma, taste, and texture, and data were analyzed using ANOVA with a DMRT follow-up test at the 0.05 level. Results indicated that the addition of wild bee honey (Apis dorsata) to liquid eggs stored at 4°C significantly improved the sensory attributes of egg whites, including color, odor, texture, and taste, but showed no significant effect on the sensory properties of egg yolks. Overall, liquid eggs with forest honey were acceptable to panelists and have the potential to be developed as a value-added food ingredient